If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -13 = -31 Reorder the terms: -13 + -1x = -31 Solving -13 + -1x = -31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -1x = -31 + 13 Combine like terms: -13 + 13 = 0 0 + -1x = -31 + 13 -1x = -31 + 13 Combine like terms: -31 + 13 = -18 -1x = -18 Divide each side by '-1'. x = 18 Simplifying x = 18
| -6=3u4+12 | | y=4(-3)+3 | | 3x^2+15x+25= | | -6x^2-20x+16=0 | | (9x+2)(9x-1)=x | | 3x-17=x-1 | | 16x^4-64=0 | | 2x+11=43-3x | | 15-2(4)= | | 4n+12=4n+12 | | h+11.3=-11.3 | | 15-2(2)= | | 3x-5=72 | | a(n+1)= | | h=-8t^2+63 | | F(x)=62+35log(11-4) | | 12x+3=32 | | -6+2(10)= | | 0.6x-14=0.4x | | f(x)=9x^2+3x-2 | | 9x+3y-36=0 | | -6+2(2)= | | 9x^4+9x=0 | | 2h=-16t^2+126t | | 2(15)-15= | | 2(9)-15= | | 5(x+3)-8(x+3)+x(5-2)= | | 3+5=57 | | 2y-8+y-5=13 | | 18x-8y=14fory | | -2=17-g | | (k+7)x=5k+3-6y |